ANALISIS PEMUTUSAN HUBUNGAN KERJA AKIBAT ADANYA DEMOSI PADA PEKERJA PT JOHNSON HOME HYGIENE PRODUCTS (STUDI KASUS PUTUSAN MAHKAMAH AGUNG RI NOMOR 566 K/PDT.SUS-PHI/2014) - Monica .; Stanislaus Atalim (Fakultas Hukum Universitas Tarumanagara, 2018)
Demotion is the decline in the position of the labor/ worker carried out by the company caused by the violation of the rules applicable within the company (indiscipline) which involves the decrease of authority, responsibility, status, facilities, even the salary earned from the company workers. This research is motivated by the implementation of termination of employment done by the company because the worker refuse to be demoted. The demotion made by the company is not caused by errors or violations committed by the worker / labor concerned but because of the restructuring department (the reason for efficiency). This study aims to analyze how the demotion validity that occurs in the worker of the company concerned and how the settlement process of termination of employment. This research was conducted by normative law research method that is by examining primary, secondary, and other non-legal material material supported by interview result. The results of the author shows that the demotion made by the company are not legitimate and not autonomously regulated in the company so that the termination of employment made by the company is an unfounded termination. This scientific study recommends the importance of the autonomous demotion regulation for the protection of workers.